Channel bar for Land Bank Development in Mempawah District - Pahlevi, Windra; Anshari, Gusti Zakaria; Nafsiatun, Nafsiatun (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2024)
Channel bar has drawns public attention because the ownership of this channel bar is not yet defined. This research investigated the fluctuation of channel bar sizes between 1972 and 2022,, and addressed the potential of channel bar as a land bank. The research was conducted in Mempawah District, West Kalimantan Province. Landsat spatial data and aerial photographs of drone were used. A number of interviews were done to understand the potential of this channel bar as a land bank. Spatially and temporally, the channel bar in Mempawah District is fluctuated, with the current area of 646 ha. The dominant land cover of this channel bar is mangrove, which plays an important role in coastal abrasion prevention. Therefore, the use of channel bar as a land bank is potentially to protect mangrove, with fully participation of local communities. One of potential uses is to develop ecotourism, and designated a channel bar land bank for mangrove protection in the District spatial planning.